DESIGNING POWERPOINT-BASED LEARNING MULTIMEDIA FOR RECOUNT TEXTS - Purboyo, Bayu Aji; Sudarsono, Sudarsono; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to design and to develop powerpoint-based learning multimedia for recount texts and to evaluate whether or not the multimedia is feasible for teaching recount text to Year-9 Students of SMP N 19 Pontianak. The multimedia consists of instructions to use it, learning objectives, materials about recount texts, examples of recount texts, and questions regarding recount text itself, as well as the score to students work on the questions. The materials were taken from students’ and teachers’ book that the researcher had simplified. The presence research was Research and Development (R&D). The procedures were adapted from ADDIE Model proposed by Hannafin and Peck Model (1987), it uses three phases approach: Analysis, Design and Development. The guideline to do the research was the result of analysis phase. From the analysis phase the researcher has figured the challenges faced by the students and the teacher. Based on the questionnaire given to the students, most of them answered that learning Recount text by using multimedia was interesting and helpful. Design phase covered all the aspects which became the focus of the multimedia, the curriculum used by the school, the roles of the teacher and students, the materials selected, and structure of the multimedia. The development phase was conducted to develop and to evaluate the powerpoint-based learning multimedia. The evaluation result shows that the multimedia was classified as very good with score 85.71% by the expert. According to the result of evaluation phase, the multimedia is considered to be feasible to be applied by the teachers to teach Recount text.Keywords: Powerpoint, Multimedia, Recount text.